Glass Ceiling Experiences of Women Administrators in Educational Organizations - Ruhi Sarpkaya; Pınar Yengin Sarpkaya; Filiz Tanrısevdi (Anı Publishing, 2019)
The aim of this study was to reveal the obstacles faced by women administrators in public educational organizations in the education zone of Efeler district of Aydın province. In the qualitative research tradition, the research, which is planned according to the interpretive phenomenology pattern, is in the interpretive phenomenology pattern, not descriptive, because it focuses on the experiences of women managers and the understanding that these experiences carry for them. The study group consisted of 22 female managers. The primary data of the study were collected using semi-structured interview technique. The interviews were carried out with the help of an information form prepared on the basis of literature and previous research. Descriptive method was used in the analysis of the primary data of the study. As a result of the research; it was understood that the participants decided to become executives for professional reasons, female managers could bring significant advantages to the education organizations where they worked, and that the social reasons were the main reasons for the lack of female managers in the educational organizations. Based on the results of the research, various recommendations have been made such as guidance of experienced managers and / or teachers to new women managers, who have just started to work in the organization, examining the phenomenon of competition among women through qualitative or quantitative research.